The prevalence, characteristics and outcomes of anomalous left coronary artery from the pulmonary artery at the Chris Hani Baragwanath Academic Hospital over a 28-year period - Chhiba, A.-L.; Cilliers, A. (SA Heart Journal, 2025)
Background: Anomalous left coronary artery from the pulmonary artery (ALCAPA) accounts for 0.25% - 0.5% of congenital cardiac disease. ALCAPA results in myocardial ischaemia and a dilated left ventricle with impaired systolic function which can be reversed postsurgical correction. We describe the presenting clinical features, diagnostic findings (including classical electrocardiographic findings) and post-operative outcomes, including the improvement in left ventricular function, in patients at a South African tertiary care centre. Methods: A retrospective analysis of patients with ALCAPA over a 28-year period at the Chris Hani Baragwanath Academic Hospital (CHBAH). Results: A total of 38 patients were included, with 24 (63.2%) females, and a median age at diagnosis of 4.6 months (IQR: 3.2 - 9.1 months). The clinical presentation was variable and included dyspnoea, poor feeding, and a cough. The majority were diagnosed to have a lower respiratory tract infection (71%). Cardiomegaly on chest X-ray (CXR) was present in 84.2% of patients. Deep Q waves in leads I and aVL was the most prevalent finding on electrocardiography in 96.9% of patients. ST segment depression (8 patients) and T wave inversion (21 patients) was evident in the lateral and inferior diaphragmatic leads. Left ventricular ejection fraction (LVEF) improved significantly from 38.8 ± 6.3% to 57.5 ± 9.1% post-surgical correction (p-value=0.0004) at the first follow up (median of 1.3 months). The early mortality rate was 21.6%. Conclusion: The clinical presentation is often suggestive of a chest infection and cardiomegaly on CXR is common. Specific electrocardiographic features commonly present in patients with ALCAPA may be a guide to making the diagnosis. Surgical correction is associated with improved left ventricular function.